Peningkatan Profil Pelajar Pancasila Aspek Kemandirian Belajar dengan Penguasaan Konten Model Cooperative Learning Menggunakan Thinglink - Malthelda Yulianti (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to identify whether content mastery using Thinglink can improve the profile of Pancasila students in the aspect of independent learning. The research subjects were students of class X IPA-1 at SMA Negeri 2 Yogyakarta for the 2022/2023 academic year.The research method is to make thorough observations using instruments made by researchers based on the theoretical basis used in the research. Descriptive qualitative techniques are data analysis techniques used in this study, to explain activity data in cycles from the stages of planning, action, observation and reflection. The results of the study explained that class X IPA 1 students experienced an increase in the ability of Pancasila student profiles in the aspect of learning independence. In the aspect of self-awareness and the situation at hand, before the action was 77.22%, at the end of cycle II it became 88.33%. The data shows an increase in self-awareness and the situation faced by 11.11%. The aspect of self-regulation learning in regulating metacognition before action was 81.94%, after cycle II it increased to 89.58%. Improved aspects of self-regulation learning in regulating metacognition by 7.64%. Aspects of self-regulation learning in managing motivation, the initial data is 79.78%, the completion of cycle II action reaches 86.11%. Self regulation learning in managing motivation increases 6.33%. The aspect of self-regulation learning in regulating behavior before action is 65.28%, after cycle II it becomes 83.33%. Increasing the aspect of self-regulation learning in regulating behavior increased by 18.05%. So it can be concluded that the content mastery service of the cooperative learning model using Thinglink can increase the profile of Pancasila students in the aspect of student learning independence.